Análisis al marco legal de la figura de la hipoteca inversa – con enfoque a los adultos mayores - Neira Balcazar, Miguel Ángel (2024)
This research study conducts a thorough examination of the concept of reverse mortgages as a specialized financial avenue for senior citizens. This financial instrument empowers them to leverage real estate acquired in their earlier years, serving as a means to generate income in lieu of a retirement pension or as supplementary source of financial support. Furthermore, the analysis encompasses an evaluation of the state of the pension system instituted by the Ecuadorian Institute of Social Security. It addresses the challenges faced by the growing population of older adults when accessing financial services. Moreover, the study acknowledges the prioritization of housing investment over other real estate options within the Ecuadorian population. This strategic investment aims to facilitate the generation of monthly income crucial for sustaining daily expenses during the elderly stage, particularly considering the prevalent absence of a retirement pension among this demographic. In the segment dedicated to comparative law the, the regulatory frameworks surrounding reverse mortgages in Spain, Puerto Rico, and Canada are meticulously scrutinized. Notably, the focus on Canada is accentuated due to the heightened relevance spurred by the Covid-19 pandemic. The fieldwork encompassed surveys administered to legal professionals actively engaged in their practice, coupled with interviews conducted with individuals specializing in financial matters and issues affecting the elderly. This comprehensive approach has enabled the identification of a discernible gap, revealing that older adults currently lack viable financial alternatives to leverage their accrued assent, hindering their ability to access loans resembling a pension. Moreover, grounded in empirical data it becomes evident that the combination of an increasing life expectancy and a declining birth rate has contributed to Ecuador again population. Remarkably, a substantial portion of this population remain unaffiliated with the Ecuadorian pension system, a circumstance contrary to the acknowledgment of it as a fundamental human right. Notably, this population segment in devoid of specialized financial alternatives to secure a pension. 5 The study concludes with propositional advocating for the implementation and regulation of reverse mortgages through legislative means. This proactive measure proposes the recognition of reverse mortgages as a distinctive financial avenue for the elderly to generate a consistent and stable income from their real estate assets. The recommendations further underscore the importance of considering the involved parties in the reverse mortgage contract and advocating for the support of this financial product, particularly for those older adults lacking a retirement pension